A rat model of post-traumatic stress disorder reproduces the hippocampal deficits seen in the human syndrome - Goswami, Sonal; Samuel, Sherin K.; Rodríguez Sierra, Olga; Cascardi, Michele; Pare, Denis (Frontiers in Behavioral Neuroscience, 2012)
Despite recent progress, the causes and pathophysiology of post-traumatic stress disorder (PTSD) remain poorly understood, partly because of ethical limitations inherent to human studies. One approach to circumvent this obstacle is to study PTSD in a valid animal model of the human syndrome. In one such model, extreme and long-lasting behavioral manifestations of anxiety develop in a subset of Lewis rats after exposure to an intense predatory threat that mimics the type of life-and-death situation known to precipitate PTSD in humans. This study aimed to assess whether the hippocampus-associated deficits observed in the human syndrome are reproduced in this rodent model. Prior to predatory threat, different groups of rats were each tested on one of three object recognition memory tasks that varied in the types of contextual clues (i.e. that require the hippocampus or not) the rats could use to identify novel items. After task completion, the rats were subjected to predatory threat and, one week later, tested on the elevated plus maze. Based on their exploratory behavior in the plus maze, rats were then classified as resilient or PTSD-like and their performance on the pre-threat object recognition tasks compared. The performance of PTSD-like rats was inferior to that of resilient rats but only when subjects relied on an allocentric frame of reference to identify novel items, a process thought to be critically dependent on the hippocampus. Therefore, these results suggest that even prior to trauma, PTSD-like rats show a deficit in hippocampal-dependent functions, as reported in twin studies of human PTSD.